Total Synthesis and Biological Evaluation of the Antibiotic Lysocin E and Its Enantiomeric, Epimeric, and N‐Demethylated Analogues1. Issue 5 (11th December 2014) - Murai, Motoki; Kaji, Takuya; Kuranaga, Takefumi; Hamamoto, Hiroshi; Sekimizu, Kazuhisa; Inoue, Masayuki
Abstract Lysocin E, a macrocyclic peptide, exhibits potent antibacterial activity against methicillin‐resistant Staphylococcus aureus (MRSA) through a novel mechanism. The first total synthesis of lysocin E was achieved by applying a full solid‐phase strategy. The developed approach also provides rapid access to the enantiomeric, epimeric, and N‐demethylated analogues of lysocin E. Significantly, the antibacterial activity of the unnatural enantiomer was comparable to that of the natural isomer, suggesting the absence of chiral recognition in its mode of action.